T helper cell recognition of muscle acetylcholine receptor in myasthenia gravis. Epitopes on the gamma and delta subunits. - Manfredi, A A (1993)
We tested the response of CD4+ cells and/or total lymphocytes from the blood of 22 myasthenic patients and 10 healthy controls to overlapping synthetic peptides, 20 residues long, to screen the sequence of the gamma and delta subunits of human muscle acetylcholine receptor (AChR). The gamma subunit is part of the AChR expressed in embryonic muscle and is substituted in the AChRs of most adult muscles by an epsilon subunit. The delta subunit is present in both embryonic and adult AChRs. Adult extrinsic ocular muscles, which are preferentially and sometimes uniquely affected by myasthenic symptoms, and thymus, which has a still obscure but important role in the pathogenesis of myasthenia gravis, express the embryonic gamma subunit. Anti-AChR CD4+ responses were more easily detected after CD8+ depletion. All responders recognized epitopes on both the gamma and delta subunits and had severe symptoms. In four patients the CD4+ cell response was tested twice, when the symptoms were severe and during a period of remission. Consistently, the response was only detectable, or larger, when the patients were severely affected.